Multiplier Effect Ekosistem Ekonomi Dam Haji: Urgen dan Esensi Prospektif Policy - Affan Rangkuti, Mahmudi (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
The activities related to Dam Haji not only impact the rights of protection for pilgrims in fulfilling the requirements, obligations, and pillars of the pilgrimage. There is a multiplier effect from these activities that occurs annually. This impact is closely related to the reduction of extreme poverty and stunting, and the realization of economic entities in the second and third sectors, directed by policies concerning the Hajj economic ecosystem. To date, there is no definitive rule of law that governs the payment, implementation, and distribution of Dam Haji. Detailed data on these Dam Haji activities are also not available. Meanwhile, support from Hajj stakeholders, Islamic community organizations, and the results of Hajj discussions recommend that the state should ensure the proper management of Dam Haji for social and economic benefits to both countries. This management represents state intervention, specifically through the Ministry of Religious Affairs, which should use its discretionary power as a regulator to issue regulations as the legal basis that must be followed by all stakeholders and the public.